PERANAN DINAS PARIWISATA DAN KEBUDAYAAN DALAM UPAYA PELESTARIAN PENINGGALAN SEJARAH DI KECAMATAN TANJUNG PURA KABUPATEN LANGKAT - Dewi, Sundari Eka; Ibrahim, Bedriati; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: In Indonesia a lot of historical relics are scattered in various regions ranging from Sabang to Maruke. The historical legacy itself consists of various forms such as fossils, equipment from the past, inscriptions, statues, buildings, manuscripts, and stories or saga. In North Sumtera Province, especially in Langkat District, Tanjung Pura Subdistrict. Historical legacy of the form of the building still stands firmly the heritage buildings of Langkat Sultanate and Dutch. The purpose of this study is to (1) knowing the history and condition of heritage in the District of Tanjung Pura Langkat Regency (2) knowing the efforts of Tourism and Culture Department in preserving the historical heritage in Tanjung Pura Sub-district of Langkat Regency (3) know the role of Tourism and Culture Department in developing tourist attraction in Tanjung Pura Sub-district Langkat Regency (4) knowing the supporting factors and inhibiting factors of Tourism Department In the Effort of Preservation of Historical Heritage in Tanjung Pura Sub-district Langkat Regency.The research method used by the writer is historical method, with qualitative descriptive approach, and using data collection techniques such as literature study, observation, interview and documentation. Historical relics residing in Tanjung Pura sub-district mostly leftover from Langkat Sultanate and as heritage again Dutch. The condition of the two historical relics is well maintained and there are not maintained. The effort of Tourism and Culture Office in preserving historical heritage in Tanjung Pura sub-district is not maximal. Similarly, in developing the historical tourism object of Tourism and Culture Department in its performance has not been maximal yet. So it raises several supporting factors and inhibiting factors in the performance process in carrying out its duties and functions. This should make the Department of Tourism and Culture continue to move everything to achieve the mission and vision to be achieved.Key Words: Role, Preservation, Heritage